Implementation of User-Centered Design Method in the Development of Tangkolo Village Website Based on User Experience to Improve Mobile Accessibility - Donaningrum, Leli (Journal of Applied Information System and Informatic (JAISI), 2024)
In the era of digital transformation, village websites have an important role as a medium of information and public services. However, unattractive website design and low accessibility, especially on mobile devices, are obstacles in creating an optimal user experience. This research aims to improve the quality of Tangkolo Village website using User-Centered Design (UCD) approach. By involving users in every stage of design, this research created an intuitive and responsive prototype. Usability measurements using the System Usability Scale (SUS) provided quantitative data to evaluate the quality of the interface. The results showed that implementing UCD significantly improved accessibility, efficiency, and user satisfaction. These findings confirm the importance of a user-centered design approach in creating inclusive digital experiences and supporting transparency of public services in villages.Keywords: Village website, User-Centered Design (UCD), accessibility, user experience, System Usability Scale (SUS), responsive design, digital transformation.